Faktor Resiko Faktor Resiko Yang Mempengaruhi Kejadian Tuberkulosis (Tb) Paru di Wilayah Kerja Puskesmas Perbaungan - Susanto Sipayung, Jenni; Hidayat, Wisnu; Silitonga, Evawani M (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2023)
Tuberculosis is a disease caused by Mycobacterium Tuberculosis bacterium. According to WHO (2021), 9.9 million people have died due to Pulmonary Tuberculosis. One of the factors affecting Tuberculosis incidents is the environment. The research aims to find out the factors affecting the incidents of Pulmonary Tuberculosis TB) in the working area of the Public Health Center (Puskesmas) of Perbaungan in 2022. Risk factors investigated encompass occupancy density, ventilation, temperature, humidity, lighting, as well as home floor and walls condition. This is a quantitative research that uses case-control. 96 respondents are used as samples encompassing 48 cases and 48 controls. Data are analyzed using chi-square and binary logistic regression tests. Based on bivariate test results, it is found that the occupancy density (0.014), ventilation (0. 038), humidity (0. 008), lighting (0. 002), home floor condition (0. 000) dan home wall condition (0.002) are the factors affecting the incidents of Tuberculosis (p-value <0.05) while temperature (0.540) is not the factor that can affect the incidents of Tuberculosis (p-value >0.05). It is suggested that Puskesmas frequently monitor and give counseling related to Tuberculosis and the society clean their houses regularly and keep the house clean. Keywords : Puskesmas Perbaungan, Pulmonary Tuberculosis, Risk Factors",